Evaluation of a treadmill with integrated force plates for kinetic gait analysis of sound and lame dogs at a trot - Brebner, N. S.; Moens, N. M. M.; Runciman, J. R. (Veterinary and Comparative Orthopaedics and Traumatology, 2006)
The objective was to compare mean peak vertical force (PVF) obtained with a treadmill with two integrated force plates (TM) with the piezoelectric force platform (FP) for sound and lame dogs at a trot. The aim was also to report the inter-step variability (ISV) for both systems and the effect of lameness on these values. Six sound dogs (20.0–25.5 kg) and six dogs with a grade 2/5 forelimb lameness (17.0–36.1 kg) were used in the study. Dogs were acclimatized and assigned an individual target velocity (1.8–2.2 m/s). Mean PVF measurements were obtained for both TM and FP. Subject velocity was controlled by belt speed on TM and restricted to 0.25 M/s above or below the assigned target velocity for FP. Acceleration was limited to +/- 0.3 M/s2. For the sound dogs, concordance and correlation coefficients of the mean PVF for the front limbs was 0.79 and 0.76, respectively. Concordance and correlation for the rear limbs was 0.90 and 0.81, respectively. For the lame dogs, concordance and correlation for the front limbs was 0.73 and 0.59, respectively. Concordance and correlation for the rear limbs was 0.89 and 0.95, respectively. ISV was 0.94 with TM and 0.84 with FP for the sound dogs and 0.96 with TM and 0.87 with FP for the lame dogs. In conclusion, TM provided rapid PVF measurements, good concordance for the hind limbs, and substantial concordance for the forelimbs in both sound and lame dogs at a trot as compared to FP. Both systems demonstrated excellent ISV for both lame and sound dogs.
Keywords: Treadmill; kinetic; gait analysis; force plate; dog